Challenging U.S. Apartheid : Atlanta and Black Struggles for Human Rights, 1960-1977 - Grady-Willis, Winston A. (Book collections on Project MUSE., 2006)
"Challenging U.S. Apartheid is an innovative, richly detailed history of Black struggles for human dignity, equality, and opportunity in Atlanta from the early 1960s through the end of the initial term of Maynard Jackson, the city's first Black mayor, in 1977. Winston A. Grady-Willis provides a seamless narrative stretching from the student nonviolent direct action movement and the first experiments in urban field organizing through efforts to define and realize the meaning of Black Power to the reemergence of Black women-centered activism. The work of African Americans in Atlanta, Grady-Willis argues, was crucial to the broader development of late-twentieth-century Black freedom struggles." "Grady-Willis describes Black activism within a framework of human rights rather than in terms of civil rights. As he demonstrates, civil rights were only one part of a larger struggle for self-determination, a fight to dismantle a system of inequalities that he conceptualizes as "apartheid structures." Drawing on archival research and interviews with activists of the 1960s and 1970s, he illuminates a wide range of activities, organizations, and achievements, including the neighborhood-based efforts of Atlanta's Black working poor, clandestine associations such as the African American women's group Sojourner South, and the establishment of autonomous Black intellectual institutions such as the Institute of the Black World. Grady-Willis's chronicle of the politics within the Black freedom movement in Atlanta brings to light overlapping ideologies, gender and class tensions, and conflicts over divergent policies, strategies, and tactics. Book jacket."--Jacket